Milk offtake, growth and feeding habits of camels in the southern rangelands of Ethiopia - Dessalegne, B. (International Livestock Centre for Africa, 1985)
Outlines the results of a study on milk offtake feeding habits and growth of camels carried out at Beke in the southern rangelands of Ethiopia. Summarises milk offtake per camel per day & month, birth weight, daily growth rate of camel calves, growth during the four seasons of the year, daily activity period occupied by different activities, plant species browsed/grazed and time spent on each during the four seasons, and chemical analysis of major browse species consumed.